Ceramide in Stem Cell Differentiation and Embryo Development: Novel Functions of a Topological Cell-Signaling Lipid and the Concept of Ceramide Compartments. (13th December 2010) - Bieberich, Erhard
Abstract : In the last two decades, the view on the function of ceramide as a sole metabolic precursor for other sphingolipids has completely changed. A plethora of studies has shown that ceramide is an important lipid cell-signaling factor regulating apoptosis in a variety of cell types. With the advent of new stem cell technologies and knockout mice for specific steps in ceramide biosynthesis, this view is about to change again. Recent studies suggest that ceramide is a critical cell-signaling factor for stem cell differentiation and cell polarity, two processes at the core of embryo development. This paper discusses studies on ceramide using in vitro differentiated stem cells, embryo cultures, and knockout mice with the goal of linking specific developmental stages to exciting and novel functions of this lipid. Particular attention is devoted to the concept of ceramide as a topological cell-signaling lipid: a lipid that forms distinct structures (membrane domains and vesicles termed "sphingosome"), which confines ceramide-induced cell signaling pathways to localized and even polarized compartments.